Effects of post-processing on the thermomechanical fatigue properties of laser modified NiTi. (January 2019) - Panton, B.; Michael, A.; Zhou, Y.N.; Khan, M.I.
Highlights: Laser processing was used to locally tune the material composition. Microstructural analysis noted change from processing and thermomechanical treatment. Mechanical performance was evaluated and compared to microstructure. Processed wire fatigue was akin to commercial wire after thermomechanical treatment. Abstract: The multifunctional capabilities needed for advanced shape memory alloys (SMA) actuators has been shown to be achievable by locally tuning the properties through laser processing. Before the wide-spread use of these SMAs is realized, a detailed understanding on the long-term stability and functional life span of these material must be achieved. The current study systematically investigates the effects of thermomechanical treatment on laser modified NiTi wires, while comparing them to the original base material. Surface analysis was done using a scanning electron microscope (SEM), while microstructure analysis was performed using transmission electron microscopy (TEM). Mechanical properties were assessed using standard tensile tests and a custom built thermomechanical fatigue. Results showed that the coarse-grains, large inclusions and surface defects associated with as laser modified NiTi resulted in reduced mechanical performance. However, subsequent thermomechanical treatment restored the refined microstructure and mechanical performance similar to the base material while providing the added functionality, thus allowing for laser processed NiTi to be used for manufacturing multiple memory NiTi actuators.